Wheezing and dyspnoea caused by aberrant left innominate artery. Issue 6 (5th October 2017) - Hayashi, Masamichi; Imaizumi, Kazuyoshi; Hattori, Hidekazu; Toyama, Hiroshi; Okazawa, Mitsushi
Abstract : We present a rare case of a branching anomaly of the aortic arch that resulted in wheezing and dyspnoea. The patient was a 60‐year‐old male with severe wheezing from babyhood, originally diagnosed with severe bronchial asthma. On auscultation, the inspiratory and expiratory wheezes appeared when the patient leaned forward. He also had difficulty in swallowing solid mass. Tests for airway reversibility and hyperresponsiveness were negative, and asthma treatment was ineffective. He had a right aortic arch. A barium oesophagogram and endoscopic examination indicated narrowing of the oesophagus from behind. Three‐dimensional reconstruction of enhanced chest CT images indicated a right aortic arch and an aberrant enlarged left innominate artery, which compressed and narrowed the oesophagus and trachea from behind. Although the patient had been diagnosed with intractable bronchial asthma, his symptoms were more likely caused by this mechanical narrowing as wheezing and dyspnoea disappeared completely after total aortic arch replacement operation. Abstract : We present a rare case of a branching anomaly of the aortic arch that resulted in wheezing and dyspnea. The patient was a 60‐year old male with severe wheezing from babyhood, originally diagnosed with severe bronchial asthma. Careful examination and testing indicated a right aortic arch and an aberrant enlarged left innominate, which compressed and narrowed the esophagus and trachea from behind. Although the patient had been diagnosed with intractable bronchial asthma, his symptoms were more likely caused by this mechanical narrowing since wheezing and dyspnea disappeared completely after total aortic arch replacement operation.